PARASITOS NOS CULTIVOS DE PIRARUCU (Arapaima gigas): Parasites in pirarucu (Arapaima gigas) farms - Teixeira Viana, Jhonatas; Santos, Alvaro Luccas Bezerra dos (Arquivos de Ciências do Mar, 2022)
In Brazil, one of the main native species cultivated is the pirarucu (Arapaima gigas), a fish that has favorable characteristics for cultivation and commercialization. However, with the intensification of fish-farming, diseases also appear, with emphasis on parasites. Observing the scarcity and dispersion of information on the subject, the present work proposed to compile the species already reported in parasitism interaction with A. gigas and the practical implications for the fish farming. It was found 38 species of parasites are known, grouped into 11 large taxonomic groups, and these parasites mainly intestine, stomach, skin, gills and fins. The survey carried out reveals the great diversity of parasites that can affect pirarucu fish farms, reaffirming the need and importance of an adequate health monitoring and a correct management practices, ensuring the animal welfare and the food security. Keywords: fish farming, native species, sanity